2017
DOI: 10.1080/08870446.2017.1320797
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between feelings and beliefs about condoms as predictors of their use

Abstract: Affective associations are a behaviour-specific and proximal predictor of condom use, mediating the effect of cognitive beliefs, suggesting they may be a particularly viable intervention target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(80 reference statements)
1
8
0
1
Order By: Relevance
“…He also found that when examining associations of affect and health behaviours, general positive and negative affect were more important in predicting intentions than were specific emotions. Ellis et al (2017) demonstrated that both affective associations and cognitive beliefs were associated with intentions, cognitive beliefs were associated with behavioural stimuli and intentions only via affective associations. Both studies are examples of the importance of taking a nuanced approach to understanding how different types of affect predict health behaviours and how these relate to cognitive predictors .…”
Section: Basic Empirical Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…He also found that when examining associations of affect and health behaviours, general positive and negative affect were more important in predicting intentions than were specific emotions. Ellis et al (2017) demonstrated that both affective associations and cognitive beliefs were associated with intentions, cognitive beliefs were associated with behavioural stimuli and intentions only via affective associations. Both studies are examples of the importance of taking a nuanced approach to understanding how different types of affect predict health behaviours and how these relate to cognitive predictors .…”
Section: Basic Empirical Papersmentioning
confidence: 99%
“…Two studies (Ellis, Rajagopal, & Kiviniemi, 2017;Kiviniemi, 2017) examine the complexity of positive and negative affect and health decisions, providing further tests of positive affect frameworks (Van Cappellen et al, 2017) and taking a nuanced approach that examines basic questions about types of affective influences and their associations with social-cognitive determinants (Carpenter & Niedenthal, 2017). Kiviniemi (2017) disentangled positive and negative affective associations with health behaviours, as well as associations involving specific emotions vs. generalised affect.…”
Section: Basic Empirical Papersmentioning
confidence: 99%
“…Affect can also signal the value of behaviors themselves. For example, positive emotions linked with behaviors serve as information about these behaviors, increasing likelihood of participation (Ellis, Rajagopal, & Kiviniemi, 2018;Karlsson, 2012;Kiviniemi, 2018;Kiviniemi & Duangdao, 2009;Van Cappellen, Rice, Catalino, & Fredrickson, 2018). Indeed, creating positive affective associations by linking condom use or healthy foods to positive words and images results in healthier behavior (Ellis, Homish, et al, 2015;Walsh & Kiviniemi, 2014).…”
Section: Current Integral Affectmentioning
confidence: 99%
“…One weakness of these models is that they tend to assume people's use of more deliberate, cognitive processing of information with less consideration of automatic, affective processes (McEachan et al 2011). Evidence suggests that affective processes are often stronger or more proximal predictors of many health decisions (Keer, van den Putte, and Neijens 2010), including the use of condoms and long-acting reversible contraceptives (Ellis, Rajagopal, and Kiviniemi 2018;Glasier, Scorer, and Bigrigg 2008;Norton et al 2005).…”
Section: Affective and Cognitive Processes In Health Decision-makingmentioning
confidence: 99%
“…The two routes commonly work together, although the affective route is often more quickly initiated and often drives later processing (Kahneman 2011). These dual processes are particularly important to understanding sexual behaviours and contraceptive use in particular (Ellis, Rajagopal, and Kiviniemi 2018;Gutnik et al 2006).…”
Section: Affective and Cognitive Processes In Health Decision-makingmentioning
confidence: 99%